Nonlinear energy-based control method for aircraft dynamics - Akmeliawati, Rini; Mareels, I. (2002)
In this paper, we approach control of aircraft dynamics from an energy perspective. The method is based on the passivity-based control technique, and similar to Total Energy Control Systems (TECS). The aircraft dynamics are presented through the energy functions. By modifying these functions, stabilisation and tracking can be achieved. The method is illustrated on an automatic landing system problem for a twin-engine civil aircraft, developed by Group for Aeronautical Research and Technology in Europe (GARTEUR). To deal with the separation of the short-period and the phugoid dynamics, we use ideas from singular perturbation theory. Disturbance rejection and robustness analysis are performed via Monte Carlo simulations. The proposed control laws behave well even under extreme flight conditions